Is it time to step outside the laboratory? The feasibility of field-based examination of exercise-induced hypoalgesia in elite badminton athletes with and without knee pain - Coombes, B. K.; Mendis, M. D.; Leung, F.; Hides, J. A. (Translational Sports Medicine, 2024)
Aim. To investigate the feasibility of testing exercise-induced hypoalgesia (EIH) in a field setting. The effect of knee pain on EIH was also explored. Design. Within-group pre-post design.